AB0398 Dispositional optimism and depression severity in early arthritis patients treated with adalimumab and DMARD-combination therapy in the improved study. (23rd January 2014) - Heimans, L.; Wevers-de Boer, K.; Visser, K.; van Groenendael, J.; Lard, L.; de Sonnaville, P.; van der Mast, R.; Giltay, E.; Huizinga, T.; Allaart, C.
Abstract : Objectives: Chronic inflammation is associated with depressive symptoms and low positive affect. We aimed to assess dispositional optimism and depression severity in patients with early arthritis after one year of remission induction therapy. Methods: In the IMPROVED-study patients with early rheumatoid and undifferentiated arthritis were treated with methotrexate (MTX) 25mg/week and 60mg/day of prednisone, tapered to 7.5mg/day in 7 weeks. Treatment goal is remission (disease activity score DAS <1.6). Patients who did not achieve early remission after 4 months were randomized to either a combination of hydroxychloroquine (HCQ) 400mg/day, sulphasalazine (SSZ) 2000mg/day, MTX 25mg/week and prednisone 7.5mg/day (arm 1) or to adalimumab (ADA) 40mg/2weeks with MTX 25mg/week (arm 2). During the first year 134 patients filled out the Life Orientation Test Revised (LOT-R) to measure optimism (range 0-24) and the Beck Depression Inventory (BDI-II) to assess depression symptom severity (range 0-63) every 4 months. Scores were compared with the Wilcoxon rank sum test after four months and 1 year between patients who did and did not achieve early remission and between patients with continued early remission after 1 year and patients who lost early remission at 1 year. Results: Patients who did achieve early remission (n=91) had a significantly higher LOT (optimism) score after 4 months of initial treatment, median score 17 (interquartile range [IQR] 16-20), compared to patients who did not (n=43, median score 16; IQR 14-17, p<0.001). The BDI (depressive symptoms) scores were significantly lower in patients in early remission (median score 4; IQR 1-6) than in patients who were not (median 10; IQR 3-15; p<0.001). At 1 year treatment, the difference in median BDI scores became much more pronounced, but not so for the median optimism scores. BDI score at 1 year was median 2 (IQR 0-4) in patients who achieved remission later than 4 months versus 8 (IQR 3-14) in patients who did not (p=0.002). LOT scores were 17 (IQR 15-20) and 17 (IQR 14-18), respectively (p=0.16). BDI scores after 1 year in patients in continued early remission or who achieved later remission were similar (4; IQR 1-6 versus 2; IQR 0-4, p=0.44), LOT scores were 18 (IQR 15-21) and 17 (IQR 15-20), respectively (p=0.81). The BDI-score was 6 (IQR 2-8) in patients who lost early remission after 1 year and 4 (IQR 1-6) in those in continued remission (p=0.03), LOT scores were 17 (IQR 14-19) and 18 (IQR 15-21), respectively (p=0.09). Conclusions: In patients with early rheumatoid or undifferentiated arthritis where treatment was aimed at achieving remission, depressive symptom severity scores at 4 months and 1 year were lower if patients were in remission at those time points. Optimism scores were relatively stable over time, reflecting the trait-like character of optimism, although remission had a positive influence. Disclosure of Interest: L. Heimans Grant/Research support from: Abbott, K. Wevers-de Boer: None Declared, K. Visser: None Declared, J. van Groenendael: None Declared, L. Lard: None Declared, P. de Sonnaville: None Declared, R. van der Mast: None Declared, E. Giltay: None Declared, T. Huizinga: None Declared, C. Allaart: None Declared